Balanço patrimonial hídrico brasileiro - Cordeiro, Pedro Sbaraini (2023)
Water availability and its uses are essential for maintaining life and economic and social activities. For this reason, this research analyzed Brazilian water management from an accounting and economic perspective, intending to measure the balance sheet of water resources in Brazil and its states. The study used the Water Balance Sheet (WBS) methodology, calculating the assets, liabilities, and net worth of water resources and projecting the data for the critical years stipulated by the UN. It also estimated the availability of water by the Brazilian state, assessed the country's water situation, and investigated the possible impacts of a reduction in water consumption on GDP per capita. The findings highlighted that although Brazil has a water surplus, this situation varies between states and regions. Some states showed a residual balance close to depletion with high liability values. A reduction in water consumption could significantly decrease GDP per capita, highlighting the dependence on water resources to generate income. Based on the results, we suggest developing more robust public policies for water management, investing in technology to reduce dependence on this resource in production, improving infrastructure, strengthening evaluation and monitoring systems, and education and awareness programs. The research fills an essential gap in the existing literature by providing a detailed accounting and economic analysis of the water resources of Brazil and its states. It reveals the potential of accounting in this role. The implications are significant for Brazil's water resources management policy and practice. The work results indicate several avenues for future research that could apply the methodology to other regionalizations and further explore regional differences in the management of water resources and their use by different economic activities.